Witnessing the formation and relaxation of dressed quasi-particles in a strongly correlated electron system - Novelli, Fabio; De Filippis, Giulio; Cataudella, Vittorio; Esposito, Martina; Vergara, Ignacio; Cilento, Federico; Sindici, Enrico; Amaricci, Adriano; Giannetti, Claudio; Prabhakaran, Dharmalingam; Wall, Simon; Perucchi, Andrea; et al. (Nature Communications, 2014)
The non-equilibrium approach to correlated electron systems is often based on the paradigm that different degrees of freedom interact on different timescales. In this context, photo-excitation is treated as an impulsive injection of electronic energy that is transferred to other degrees of freedom only at later times. Here, by studying the ultrafast dynamics of quasi-particles in an archetypal strongly correlated charge-transfer insulator (La2CuO4+δ), we show that the interaction between electrons and bosons manifests itself directly in the photo-excitation processes of a correlated material. With the aid of a general theoretical framework (Hubbard-Holstein Hamiltonian), we reveal that sub-gap excitation pilots the formation of itinerant quasi-particles, which are suddenly dressed by an ultrafast reaction of the bosonic field.
CRIS-Team Scopus Importer:2022-07-20